Granparents and grandchildren in the 21st century: authority, affection and fear - Paula, Flávia Viana de; Silva, Maria Josefina da; Bessa, Maria Eliana Peixoto; Morais, Geridice Lorna Andrade de; Marques, Marília Braga (Rev Rene, 2011)
Changes occurred in families brought inside households in Brazil changes in the relationship between grandparents and grandchildren. This research aimed at learning about the speech of the elderly concerning intergenerational relationships as a child and nowadays, and also at identifying the changes they noticed in the intergenerational relations in the context of the current family as well as of their antecedents. This is a descriptive study with qualitative approach developed in the city of Fortaleza. The sample consisted of 12 elderly people, and it was used the interview technique for data collection. Data was organized by using the Collective Subject Discourse. It was noticed in the speeches that there were changes in the relationship between grandparents and grandchildren. Previously, there was a good relationship between grandparents and grandchildren, with clear rules. Currently, there are some conflicts to be taken into consideration among which is highlighted loss of authority, affection and fear.